Preventing The Impact of Unequal Thought Social Media on LGBT and HIV-AIDS In Mindset of Gen Z - Erlina Puspitaloka Mahadewi; Intan Silviana Mustikawati; Mohamad Reza Hilmy; Suryari Purnama; Arman Harahap (International Journal Of Community Service, 2024)
The present study reports the comprehensive study after pandemic era in early 2024, aims to determine an effective methodical approach in exploiting the impact of thought inequality when using social media as an effort to prevent the transmission of HIV/AIDS (LGBT) infections. The preparation of this literature review uses the narrative literature review method by entering keywords into the PubMed, ProQuest, Wiley, CINAHL and databases of ScienceDirect. The results of the research show that the effective method used in utilizing social media in efforts to prevent the transmission of HIV/AIDS (LGBT) infections including Network Monitoring Systems and direct intervention. The Network Monitoring System method can analyze the scientific role of health sociology in statistical data or social change trends which are used as material considerations in formulating health promotion policies. Meanwhile, direct intervention with a comprehensive educational approach in empowering individuals, communities or groups becomes a stimulant for one is the potential to oversee health problems independently. In conclusion, both produce outputs in the form of increasing awareness in the prevention and transmission of HIV/AIDS (LGBT), healthy sexual knowledge, minimizing stigma towards HIV/AIDS sufferers, getting accurate target tracing paths, education will be provided.